Arthroscopic surgical techniques [videorecording] : hip arthroscopy - Byrd, J. W. Thomas; Arthroscopy Association of North America; American Academy of Orthopaedic Surgeons (USA : American Academy of Orthopaedic Surgeons, 2008)
Introduction to hip arthroscopy, covering conditions that can be treated arthroscopically, strengths and limitations of the supine and lateral approaches for hip arthroscopy, the proper steps and special equipment necessary for a superior end result, the portals commonly used to perform hip arthroscopy, anatomical relations in the hip, the detailed sequence of surgical steps, and the steps necessary to avoid common pitfalls associated with treating hip conditions arthroscopically.